2018
DOI: 10.1038/s41556-018-0121-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell characterization of haematopoietic progenitors and their trajectories in homeostasis and perturbed haematopoiesis

Abstract: The dynamics of haematopoietic stem cell differentiation and the hierarchy of oligopotent stem cells in the bone marrow remain controversial. Here we dissect haematopoietic progenitor populations at single cell resolution, deriving an unbiased reference model of transcriptional states in normal and perturbed murine bone marrow. We define the signature of the naive haematopoietic stem cell and find a continuum of core progenitor states. Core cell populations mix transcription of pre-myeloid and pre-lymphoid pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
274
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(320 citation statements)
references
References 74 publications
22
274
0
Order By: Relevance
“…In early studies, high EPO levels were associated with increased HSC proliferation 15,21 . More recently, upregulation of cell cycle-related genes in HSCs following an increase of EPO levels in vivo corroborated these findings 17,18,20 . In addition, an increased EPO level was found to impact expression of immune response genes 18 or bone homeostasis-associated genes 13 in HSCs.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…In early studies, high EPO levels were associated with increased HSC proliferation 15,21 . More recently, upregulation of cell cycle-related genes in HSCs following an increase of EPO levels in vivo corroborated these findings 17,18,20 . In addition, an increased EPO level was found to impact expression of immune response genes 18 or bone homeostasis-associated genes 13 in HSCs.…”
Section: Introductionsupporting
confidence: 53%
“…EPO has been shown to also target hematopoietic niche cells (osteoblasts and osteocytes 8,9 , endothelial cells 10,9 , adipocytes 11,12 , mesenchymal stem cells 13,14 ). In the hematopoietic hierarchy, EPO has also been suggested to act on hematopoietic stem and progenitor cells 15,13,16,17,18,19,20,21 , but several aspects remain debated.…”
Section: Introductionmentioning
confidence: 99%
“…Interrogating our observed cell states using pseudotemporal ordering and comparing these to recent work that defined the signatures of various haematopoietic stem and progenitor cell states in single-cell resolution 17 allowed us to reconstruct that MDSCs form an aberrant trajectory from neutrophil progenitor cells that occurs at the cost of normal differentiation into mature neutrophil granulocytes, which are less abundant in tumor-bearing mice (Fig. 3A).…”
Section: Discussionmentioning
confidence: 96%
“…For cell type subset analyses (Monocytes and Neutrophils), clusters with high expression of cell type markers (Csf1r and Ly6g, respectively) were subset out and standard Seurat workflow was applied on each. In the case of the neutrophil-specific analysis, a population of cells that grouped together and expressed a set of markers associated with neutrophil progenitors 17 was manually labeled and treated as a distinct cluster for analysis. Starting with all cells from the WT and PyMT combined analysis, neutrophils were specifically subset out.…”
Section: In Vitro Generation Of Mdscsmentioning
confidence: 99%
“…Here we aimed to develop a new fate-mapping mouse model specific for monocyte progenitors that could precisely measure the contribution of monocytes to RTM populations under any condition and discern monocytes from DCs. The earliest monopotent BM progenitors giving rise to monocytes are common monocyte progenitors (cMoPs) (Hettinger et al, 2013), although commitment to monocytes occurs earlier as shown by single-cell mRNA sequencing (scRNA-seq) (Giladi et al, 2018;Paul et al, 2015). cMoPs are proposed to arise from the hierarchical model of common myeloid progenitor (CMP) à granulocyte-monocyte progenitor (GMP) à monocytedendritic cell progenitors (MDP) à common monocyte progenitor (cMoP) (Guilliams et al, 2018;Terry and Miller, 2014).…”
Section: Introductionmentioning
confidence: 99%